Cocconeis sawensis sp. nov. (Bacillariophyceae) from a saline lake (Sawa Lake), South Iraq: comparison with allied taxa - Al-Handal, Adil; Riaux-Gobin, Catherine; Abdulla, Dawood; Ali, Malik (Phytotaxa, 2014)
A new species of the genus Cocconeis is described. Cocconeis sawensis sp. nov. was observed as epiphyte on the macrophyte Chara Linn. sp., collected from a saline lake in Iraq (Sawa Lake). Description of the new species is based on details observed with light and scanning electron microscopy. Cocconeis sawensis belongs to a group of taxa similar to Cocconeis euglypta Ehrenberg, but differs in a number of fine ultrastructural features including stria density and hymenes, raphe, valve shape and rim, valvocopula, hymen perforations and fimbriae shape as well as a presence of a pore-like structure reminiscent of a vestigial raphe in the sternum valve. A comparison with closely related taxa is given.